Towards a sign language synthesizer: a bridge to communication gap of the hearing/speech impaired community - Maarif, Haris Al Qodri; Akmeliawati, Rini; Gunawan, Teddy Surya; Shafie, Amir Akramin (IOP Publishing, 2013)
Sign language synthesizer is a method to visualize the sign language movement from the spoken language. The sign language (SL) is one of means used by HSI people to communicate to normal people. But, unfortunately the number of people, including the HSI people, who are familiar with sign language is very limited. These cause difficulties in the communication between the normal people and the HSI people. The sign language is not only hand movement but also the face expression. Those two elements have complimentary aspect each other. The hand movement will show the meaning of each signing and the face expression will show the emotion of a person. Generally, Sign language synthesizer will recognize the spoken language by using speech recognition, the grammatical process will involve context free grammar, and 3D synthesizer will take part by involving recorded avatar. This paper will analyze and compare the existing techniques of developing a sign language synthesizer, which leads to IIUM Sign Language Synthesizer.